Analisis Problematika Riba pada Perspektif Al-Ghazali Terhadap Ekonomi Islam : Studi Kasus Kredivo - Mozza Naiara Fawwaz; Fauziah Nur Firdausha; Ayu Dwi Lestari; Lina Marlina (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
Al Ghazali and a series of ideas related to Islamic economics discuss usury in terms of achieving an integrated community economy, as well as an analysis of the Kredivo application in that context. Al Ghazali argues that usury is contrary to the function of money as a medium of exchange and a measure of value, therefore causing suffering and accumulating wealth in only a few people. He classifies two types of usury: usury an nasi'ah and usury al-faḍl, both of which are prohibited in transactions between similar goods. Lending money with interest in the context of the Kredivo application certainly violates Islamic law as the first reason, and is also related to the point that usury is contrary to the economic principles stated by Al Ghazali. Al Ghazali shows the sharia attitude that opposes arbitrary control and management of assets by emphasizing awareness of justice. Therefore, through the analyses above, it becomes clear why Kredivo is easily labeled as haram because it has the potential to harm many people, many people who are certainly not supported by welfare.